Clinical validation of reduction in cocaine frequency level as an endpoint in clinical trials for cocaine use disorder. (1st December 2019) - Roos, Corey R.; Nich, Charla; Mun, Chung Jung; Babuscio, Theresa A.; Mendonca, Justin; Miguel, André Q.C.; DeVito, Elise E.; Yip, Sarah W.; Witkiewitz, Katie; Carroll, Kathleen M.; Kiluk, Brian D.
Highlights: Sought to validate non-abstinence endpoint for cocaine dependence clinical trials. Specified three categorical frequency levels similar to WHO drinking risk levels. Levels were: 1) abstinence, 2) low: 1–4 days/month, 3) high: 5+ days/month. At least one-level reduction associated with clinical benefit following treatment. Reducing from high to low frequency also associated with clinical benefit. Abstract: Background: Despite calls for non-abstinence endpoints in randomized clinical trials (RCTs) for cocaine use disorder, there is a lack of data validating non-abstinence endpoints. We conducted a clinical validation of reduction in cocaine frequency level as a non-abstinence endpoint in RCTs for cocaine use disorder (CUD). Methods: We utilized a pooled dataset (n = 716; 63.6 % male, 51.4 % non-Hispanic white) from seven RCTs for CUD. We specified three cocaine frequency levels at baseline and end of treatment (EOT): abstinence, low frequency (1–4 days/month), and high frequency (5+ days/month). Multiple regression analyses were conducted. Results: Among the sample, 38.3 % had at least a one-level reduction from baseline to EOT, whereas 61.7 % did not change/increased frequency level. At least a one-level reduction in cocaine frequency level from baseline to EOT versus no change/increase was significantly associated with better functioning up to one year following treatment on measures of cocaine use, as well as psychological, employment, legal, and other drug use problem severity domains of the Addiction Severity Index (ASI). We also conducted analyses only among those at the high frequency level at baseline and found those who reduced to low frequency use at EOT had similar outcomes at follow-up as those who reduced to abstinence. Conclusions: At least a one-level reduction in cocaine frequency level from pretreatment to EOT can be a clinically meaningful endpoint given its relation to sustained clinical benefit up to one-year following treatment. These data parallel recent findings regarding reduction in drinking risk level among individuals with alcohol use disorder.